In-situ electropolymerization of porous conducting polyaniline fibrous network for solid-state supercapacitor - He, Yapeng; Wang, Xue; Huang, Hui; Zhang, Panpan; Chen, Buming; Guo, Zhongcheng (Applied surface science, 2019)
[Display omitted] •Insight into the growth mechanism of porous conducting polyaniline fibrous network.•Realization of controllable loading capacity of PANI combined with high specific surface area.•Solid-state supercapacitor device assembled delivers mass capacitance of 149.3 F g−1.•Low self-discharge with weak leakage current and distinct cycling stability. Polyaniline (PANI) is considered as an attractive electrode material in energy storage devices. Here, self-supported porous conducting PANI fibrous network is in-situ deposited on carbon paper (CP) via a facile electropolymerization method for solid-state supercapacitor. We also explicate the possible growth mechanism of nanofiber network based on the morphology evolution. Combined with high specific surface area (42.2–96.3 m2 g−1), controllable loading capacity (10 μg cm−2 cycle−1) and superior conductivity (1.13–1.98 S cm−1), the composite electrodes are further proved with FTIR, Raman, XPS and UV–Vis spectra. The capacitance performances are systematically investigated via cyclic voltammetry, galvanostatic charge/discharge curves and electrochemical impedance spectroscopy. As-prepared CP/PANI-80 hybrid electrode exhibits mass capacitance of 455.1 F g−1 under 0.5 A g−1 with pseudo-capacitive contribution ∼58.4%. Meanwhile, the gravimetric capacitances of composite electrodes follow a decline trend with increase of loading capacity as the effective utilization rate and specific surface area of active PANI. Then, the solid-state supercapacitor device assembled delivers mass capacitance of 149.3 F g−1 and presents admirable energy density of 13.3 Wh kg−1 with power density 80 W kg−1 in PVA/H2SO4 electrolyte. Moreover, solid-state device exhibits favorable self-discharge behavior with low leakage current as small as 27.5 µA, distinct long time cycling stability with capacitance retention of 81.6% after 4000 continuous cycles. Above encouraging results could illustrate the great promise of this method and tremendous potential of PANI fibrous network electrodes in solid-state energy-storage systems.